"I'm Not Sure What to Believe": Media Distrust and Opinion Formation during the COVID-19 Pandemic. Issue 3 (4th August 2022) - TERNULLO, STEPHANIE
Abstract : Social scientists have documented rapid polarization in public opinion about COVID-19 policies. Such polarization is somewhat unsurprising given experimental studies that show opinions on novel issues can diverge quickly in the presence of partisan frames. In this paper I describe a different process that operates alongside polarization: not centrism but a lack of opinion formation. Drawing on four rounds of in-depth interviews with 86 Midwesterners, conducted between June 2019 and November 2020, I take an inductive approach to understanding variation in the processes by which people gathered and interpreted information about COVID-19. I find that those with universal distrust in all media struggled to adjudicate between conflicting interpretations of reality, particularly if they also had low political knowledge. The result was that they felt little confidence in any opinions they formed. These findings suggest that deteriorating trust in media is an important and understudied factor shaping trajectories of opinion formation.